An Improved Automated Setup for Solubility Determination of Drugs - Ahmad Ghanbari 1, Yashar Sarbaz, Vahid Jouyban-Gharamaleki, Karim J (Tabriz University of Medical Sciences, 2016)
Background: Solubility of a drug/drug candidate is an essential information in the pharmaceutical area. Classical solubility determination method used in the laboratories are expensive and time-consuming. Attempts were made to provide an automated solubility determination setup based on a laser monitoring technique. Methods: In a previously developed setup, drug powder was added to a given quantity of the solvent which made some troubles in practical applications. The present work reports another setup which adds solvent to a given mass of the drug. The validity of the measured solubilities is checked by comparing the measured solubilities of acetaminophen at two temperatures in water and ethanol mixtures with the corresponding data from the literature. Results: The results reveal that the improved setup could overcome the limitations of the previously developed setup and could be used for drug solubility determination. Conclusion: The improved setup overcomes the troubles made in the previous setup and could be used in generating large amount of solubility data to be used in the pharmaceutical industry.